Uji Daya Hambat Bakteri Paenibacillus polymyxa terhadap Pertumbuhan Jamur Colletotrichum sp. Secara In Vitro - MAYADIANTI, IDA AYU ISTRI; KHALIMI, KHAMDAN; SUNITI, NI WAYAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.9, No.4, Oktober 2020, 2020)
Inhibition Test of  Paenibacillus polymyxa  on the Growth of the Fungus  Colletotrichum  sp . in vitro Fungus  Colletotrichum  sp. is an airborne pathogen that causes anthracnose disease in chili. Utilization of biological agents of  Paenibacillus polymyxa  is the choice in suppressing the growth and fungal attack of  Colletotrichum  sp. The use of biological agency is environmentally friendly. The purpose of this study was to determine the inhibitory properties of  P. polymxya  bacteria against the growth of the fungus  Colletotrichum  sp.  in vitro .The results showed that  P. polymyxa  isolates C1 was able to inhibit the growth of  C. acutatum  isolates BLCB,  C. gloesporioides  isolates KLCR2,  C. scovillei  isolates SGCR,  C. fructicola  isolates KRCR,  C. truncatum  isolates DPCR2 and  C. nymphae  isolates BLCR, with the percentage of inhibition ranging from 82.74% to 86.52%. Bacterial filtrate  P. polymyxa  C1 was able to inhibit the growth of fungal colonies of  C. acutatum  isolate BLCB,  C. gloesporioides  isolate KLCR2,  C. scovillei  isolates SGCR ,  C. fructicola  isolates KRCR,  C. truncatum  isolates DPCR2 and  C. nymphaeae  isolates BLCR with inhibitory power percentage ranging from 71.90% to 82.48%.